Mobilization of lipids and fortification of cell wall and cuticle are important in host defense against Hessian fly - Khajuria, Chitvan; Wang, Haiyan; Liu, Xuming; Wheeler, Shanda; Reese, John C.; El Bouhssini, Mustapha; Whitworth, R. Jeffery; Chen, Ming-Shun (My University, 2013)
Background: Wheat – Hessian fly interaction follows a typical gene-for-gene model. Hessian fly larvae die in wheat plants carrying an effective resistance gene, or thrive in susceptible plants that carry no effective resistance gene. Results: Gene sets affected by Hessian fly attack in resistant plants were found to be very different from those in susceptible plants. Differential expression of gene sets was associated with differential accumulation of intermediates in defense pathways. Our results indicated that resources were rapidly mobilized in resistant plants for defense, including extensive membrane remodeling and release of lipids, sugar catabolism, and amino acid transport and degradation. These resources were likely rapidly converted into defense molecules such as oxylipins; toxic proteins including cysteine proteases, inhibitors of digestive enzymes, and lectins; phenolics; and cell wall components. However, toxicity alone does not cause immediate lethality to Hessian fly larvae. Toxic defenses might slow down Hessian fly development and therefore give plants more time for other types of defense to become effective. Conclusion: Our gene expression and metabolic profiling results suggested that remodeling and fortification of cell wall and cuticle by increased deposition of phenolics and enhanced cross-linking were likely to be crucial for insect mortality by depriving Hessian fly larvae of nutrients from host cells. The identification of a large number of genes that were differentially expressed at different time points during compatible and incompatible interactions also provided a foundation for further research on the molecular pathways that lead to wheat resistance and susceptibility to Hessian fly infestation.
Citation: Khajuria et al.: Mobilization of lipids and fortification of cell wall and cuticle are important in host defense against Hessian fly. BMC Genomics 2013 14:423.
Keywords: Wheat; Hessian fly; Hessian fly resistance